Evidence from the Dead: New Estimates of Wealth Inequality Using the Distribution of Estates - Facundo Alvaredo; Yonatan Berman; Salvatore Morelli (Institute of Labor Economics (IZA), 2024)
This paper studies the estimation of wealth distribution using estates left at death. We establish formal conditions for adopting a simplied version of the classic estate multi- plier method, using only minimal information on estates and mortality. We empirically validate these conditions and apply the simplied approach to produce novel long-run top wealth share series for Belgium, Japan, and South Africa, where estate data have not yet been exploited. This approach may vastly expand the range of countries and years for which wealth inequality can be estimated, where estate data exist but the standard method cannot be applied.
Keywords: D3; H2; N3; 330; mortality rates; estate tax; wealth inequality; public economics